Multi-Sensory System for Spatially Aware Colonoscopy - Panula, Tuukka; Rosa, Bruno; Anastasova-Ivanova, Salzitsa; Kaisti, Matti; Lo, Benny (Institute of Electrical and Electronics Engineers (IEEE), 2026)
The traditional method of performing a colonoscopy requires a trained physician operating the instrument manually. There is no proper feedback to aid the user in the process and typically the physician has to rely solely on the camera output to guide the endoscope. This method can lead to discomfort or even colon perforation due to the elongated endoscope scratching or tearing the colon tissue. To address this issue and enable spatial awareness to the instrument, we propose a modular multi-sensor system that integrates bending, pressure, and motion sensing units into the endoscope. All sensors are manufactured using inexpensive off-the-shelf components. The proposed sensor system was characterized on a robotic test bench and validated in a colon phantom study. The results demonstrate the feasibility and robustness of the proposed sensor fusion approach in colonoscopy which has the potential for safer and more effective inspection of the bowels. The introduction of these sensing modalities to an endoscope paves the way for AI-assisted and possibly autonomous colonoscopy in the future.